1990
DOI: 10.1080/00029157.1990.10402829
|View full text |Cite
|
Sign up to set email alerts
|

Some Conditions of Compliance and Resistance among Hypnotic Subjects

Abstract: Five experimental approaches to the resolution of the century-old Bernheim/Janet dispute and the issue of involuntariness or coercion (the classical suggestion effect) are presented. Four experiments are reported that follow one of the approaches: attempts to induce hypnotic subjects to resist suggestions made in trance. The design is one in which a "resistance instructor" proposes a reward for the resisting subject. Tentative inferences from the results are that the classical suggestion effect is found with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The flip side is that subjects will continue to respond to suggestions even in the presence of reasonable pressure to resist (e.g. Connors, Barnier, Coltheart, et al, 2012;Levitt, Baker & Fish, 1990;Noble & McConkey, 1995). Levitt et al (1990) found that 50% of highs did not resist a suggestion when informed they would receive $100 if they did resist.…”
Section: Phenomenological Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The flip side is that subjects will continue to respond to suggestions even in the presence of reasonable pressure to resist (e.g. Connors, Barnier, Coltheart, et al, 2012;Levitt, Baker & Fish, 1990;Noble & McConkey, 1995). Levitt et al (1990) found that 50% of highs did not resist a suggestion when informed they would receive $100 if they did resist.…”
Section: Phenomenological Controlmentioning
confidence: 99%
“…Connors, Barnier, Coltheart, et al, 2012;Levitt, Baker & Fish, 1990;Noble & McConkey, 1995). Levitt et al (1990) found that 50% of highs did not resist a suggestion when informed they would receive $100 if they did resist. In all these cases, the subject's task is to determine what the experimenter actually wants, as the subjects will try to produce the experiences that satisfy the situational demands.…”
Section: Phenomenological Controlmentioning
confidence: 99%